2010
DOI: 10.1021/cb100245u
|View full text |Cite
|
Sign up to set email alerts
|

Minor-Groove-Modulating Adenosine Replacements Control Protein Binding and RNAi Activity in siRNAs

Abstract: Short-interfering RNAs (siRNAs) are common tools in molecular biology, however the development of RNAi-based therapeutics is limited by immunostimulatory and non-specific effects mediated by off-target RNA-binding proteins. PKR and ADAR1 are two proteins implicated in RNAi off-target effects, and share a common means of interaction with siRNAs through double-stranded RNA binding motifs (dsRBMs). Here we report the site-specific introduction of N2- propargyl 2-aminopurine into siRNAs and subsequent conversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 66 publications
(103 reference statements)
1
67
2
Order By: Relevance
“…Previous RNAi studies with a different sequence had shown that position 2 of the guide strand is sensitive to this modification whereas modification at position 14 was tolerated. [25] Here, all eight positions tested showed significantly reduced RNAi activity, with position 20 as the most tolerant to modification (~ two-fold reduction in knockdown compared to the unmodified siRNA). On the other hand, modification on the Hoogsteen face at positions 12, 15, and 20 in this sequence retains RNAi activity (Figure 4).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous RNAi studies with a different sequence had shown that position 2 of the guide strand is sensitive to this modification whereas modification at position 14 was tolerated. [25] Here, all eight positions tested showed significantly reduced RNAi activity, with position 20 as the most tolerant to modification (~ two-fold reduction in knockdown compared to the unmodified siRNA). On the other hand, modification on the Hoogsteen face at positions 12, 15, and 20 in this sequence retains RNAi activity (Figure 4).…”
Section: Resultsmentioning
confidence: 95%
“…However, base modifications to an siRNA guide strand pose the risk of disrupting essential hydrogen bonding crucial for the formation of the A-form duplex needed to activate RNAi. Previously, our lab has developed replacements for adenosine in siRNAs that maintain base pairing with uridine while altering either the Hoogsteen (7-triazolo-8-aza-7-deazaadenosines) [2223] or WC face ( N 2 -alkyl-2-aminopurines) [2425] (Scheme 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include fluorescent groups for detection or imaging and groups that alter tissue delivery and cellular uptake of the RNA (9, 23). Novel reactive “handles” also allow one to ligate fragments together generating large functional RNAs from smaller synthetic strands or to diversify an RNA structure from a single common intermediate for structure/activity relationship studies (2426). Early work on this topic included methods to introduce aliphatic amines, thiols, and aldehydes into RNA (2728).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, triazole formation with the alkyne-bearing RNA strands was efficient with primary azides, copper sulfate, sodium ascorbate and the copper binding ligand tris-(hydroxypropyltriazolylmethyl)amine. Modification of siRNAs with this procedure allowed us to probe the effect of varying minor groove substituents on RNA duplex stability, base pairing specificity, RNA interference, and the binding of known siRNA-binding proteins (26, 30). For instance, the N-ethylpiperidine derivative (9, Figure 3) had miminal effect on RNAi activity at multiple positions in an siRNA but substantially reduced off-pathway protein binding (26).…”
Section: Introductionmentioning
confidence: 99%